2017
DOI: 10.1292/jvms.16-0641
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftiofur in healthy and lipopolysaccharide-induced endotoxemic newborn calves treated with single and combined therapy

Abstract: The aim of this research was to compare plasma pharmacokinetics of ceftiofur sodium (CS) in healthy calves, and in calves with experimentally induced endotoxemia. Six calves received CS (2.2 mg/kg, IM) 2 hr after intravenous administration of 0.9% NaCl (Ceft group). After a washout period, the same 6 calves received CS 2 hr after intravenous injection of lipopolysaccharide (LPS+Ceft group). Another group of 6 calves received a combination of drug therapies that included CS 2 hr after administration of 0.9% NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 47 publications
(63 reference statements)
3
12
1
Order By: Relevance
“…Ceftiofur reached a maximum serum concentration after (2.48±0.07h) this result is similar to ceftiofur reported in cattle and water buffalo (2.00 and 2.87h , Nie et al,2015 andGorden et al,2015). The present result is nearly similar to the results in calves (1.82 and 1.5h;Halsteadet al,1992 and Altan et al,2017).however disagreed with those stated in sheep (0.81h, Craigmill et al,1997), goats (1.17h, Courtin et al, 1997), camel (1.22h, Goudah, 2007), buffalo calves (0.33h, Sudamrao,2015) and cattle (0.67h, Hornish and Kotarski 2002). After comparison to other cephalosporin, the time studied to reach the maximum serum concentration (Tmax) was agreed with those reported in cefqinome in broiler chicken (2.8h,El-Mahdy et al, 2015) The mean peak ceftiofur serum concentration (Cmax) was (6.50±0.12 μg/ml) after intramuscular administration of 2.2 mg ceftiofur /kg.bw these values are consistence with those in water buffalo (6.2μg/ml, Nie et al,2015),buffalo calves (6.6μg/ml ,Sudamrao, 2015), calves (7.73 μg/ml, Altan et al,2017), sheep (7.13μg/ml, Craigmill et al,1997) and cows (7.8μg/ml, Tohamy, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Ceftiofur reached a maximum serum concentration after (2.48±0.07h) this result is similar to ceftiofur reported in cattle and water buffalo (2.00 and 2.87h , Nie et al,2015 andGorden et al,2015). The present result is nearly similar to the results in calves (1.82 and 1.5h;Halsteadet al,1992 and Altan et al,2017).however disagreed with those stated in sheep (0.81h, Craigmill et al,1997), goats (1.17h, Courtin et al, 1997), camel (1.22h, Goudah, 2007), buffalo calves (0.33h, Sudamrao,2015) and cattle (0.67h, Hornish and Kotarski 2002). After comparison to other cephalosporin, the time studied to reach the maximum serum concentration (Tmax) was agreed with those reported in cefqinome in broiler chicken (2.8h,El-Mahdy et al, 2015) The mean peak ceftiofur serum concentration (Cmax) was (6.50±0.12 μg/ml) after intramuscular administration of 2.2 mg ceftiofur /kg.bw these values are consistence with those in water buffalo (6.2μg/ml, Nie et al,2015),buffalo calves (6.6μg/ml ,Sudamrao, 2015), calves (7.73 μg/ml, Altan et al,2017), sheep (7.13μg/ml, Craigmill et al,1997) and cows (7.8μg/ml, Tohamy, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The longer elimination time(t0.5(el)) in calves may be largely related to less maturation of eliminating organs and/or elimination processes of ceftiofur and its metabolite particularly in comparison to adult and old animals of various species (Brown et al,1996). On the opposite, lower elimination time (19.9 h) in calves (Altan et al,2017) relative to the current inquiry may be owing to varieties in the enzymatically catalyzed metabolism and ceftiofur renal excretion, including effective renal secretion through organic acid transporters, and also glomerular filtration in such animals (Brown et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, increased AUC 0–∞ of marbofloxacin in the MBX + ST + LPS group may have resulted from changes in plasma concentrations and plasma concentration–time curve. Previous studies have reported that LPS‐induced endotoxemia causes an increase in AUC of the drugs (Altan et al, 2017; Elmas et al, 2006; Waxman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%